Texture and color analysis of lentils and rice for instant meal using image processing techniques - Pieniazek, Facundo (2016)
Typical approaches for measuring color and texture properties are mostly timeconsuming. An image-based method was used to evaluate texture and color in lentils and rice subjected to freeze-drying for an instant meal. Cooked and cooked freeze-dried rehydrated lentils and rice were analyzed by scanning electron microscopy. Texture properties were analyzed by texture analyzer and image analysis. Color was performed with a digital camera. Significant differences for color and texture (P < 0.05) were observed for cooked and cooked freeze-dried rehydrated lentils and rice. A linear trend with a linear correlation was applied for mechanical and image features. Results showed that image features such as contrast, correlation, energy and homogeneity calculated from Gray-level co-occurrence matrix had high correlations with mechanical features of hardness, adhesiveness, chewiness and gumminess for lentils, and for rice, mechanical features adhesiveness, gumminess and image features homogeneity and contrast. With this approach to quality, image processing techniques can be a useful tool.